Hospital Leadership, Employee Engagement, and Nurse Retention as Components of Workplace Health Promotion in Private Religious Hospitals in Indonesia - Qurratul Aini; Rini Eka Sari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Workplace health promotion is essential in healthcare organizations because workforce well-being is closely connected to service continuity, patient safety, and organizational sustainability. Specific Background Private religious hospitals in Indonesia provide a distinctive context where professional healthcare management intersects with spiritual organizational values, leadership practices, employee support, and workforce development. Knowledge Gap Limited research has integrated hospital leadership, employee engagement, talent development, and nurse retention within a workplace health promotion framework, particularly in private religious hospitals in Indonesia. Aims This study examines how hospital leadership, employee engagement, and talent development contribute to nurse retention in private religious hospitals in Yogyakarta, Indonesia. Results Using a mixed-methods design with cross-sectional survey data, qualitative interviews, partial least squares structural equation modeling, and thematic analysis, the study found that hospital leadership was positively associated with employee engagement and talent development. Employee engagement and talent development were positively associated with nurse retention and partially mediated the relationship between leadership and retention. Qualitative findings showed that spiritual organizational culture strengthened meaning, belonging, and emotional attachment among nurses. Novelty This study positions nurse retention as an indicator of a sustainable and health-promoting work environment. Implications Leadership and talent development should be managed as workplace health promotion strategies that strengthen psychological support, professional growth, engagement, and organizational culture. Highlights: Leadership was linked with engagement and talent development. Spiritual values strengthened meaning and belonging. Professional growth partially mediated workforce continuity. Keywords: Workplace Health Promotion, Nurse Retention, Hospital Leadership, Employee Engagement, Talent Development